Embodied Knowledge in NU Pesantren: Islamic Arts, Traditional Pedagogy, and Cultural Transmission in Tasikmalaya (IJORER : International Journal of Recent Educational Research, 2026)
This study examines zapin, hadroh, and marawis as forms of embodied pedagogy within Nahdlatul Ulama (NU) pesantren in Tasikmalaya, Indonesia, based on a multi-sited ethnographic investigation involving 247 santri aged 12–24. Data were generated through 156 hours of participant observation, 42 video-documented rehearsal and performance sessions, and 18 semi-structured interviews with key pedagogical actors. Analysis identified five interconnected mechanisms shaping moral learning: somatic inscription through repetitive bodily practice, relational ensemble-based pedagogy, traditionalist epistemology as a generative constraint, gender-differentiated modes of ethical embodiment, and the longitudinal integration of learned dispositions into everyday behavior. Engagement in Islamic arts was associated with substantial gains in motor competence (70-126%), higher moral development among art-intensive cohorts (d = 0.78, p < 0.012), and sustained reductions in behavioral infractions over 24 months (62–89%, p < 0.001). The findings demonstrate that embodied artistic practice enables Islamic moral knowledge to be internalized as durable bodily habit rather than abstract instruction.